Efficacy analysis following polymer coated drug eluting stent and bare metal stent deployment for femoropopliteal arterial disease - Shehada, Yousef; Bisdas, Theodosios; Argyriou, Angeliki; Torsello, Giovanni; Tsilimparis, Nikolaos; Beropoulis, Efthymios; Stavroulakis, Konstantinos (Vascular, 2024)
Objectives The objective is to assess the performance of the Eluvia polymer coated drug eluting stent (DES) compared to a bare metal stent (BMS) platform in patients with femoropopliteal arterial disease. Methods This is a retrospective, single-center analysis. Patients treated with the Eluvia DES (group Eluvia) or the EverFlex BMS (group BMS) for femoropopliteal disease between January 2013 and December 2019 were included. Primary measure outcome of this analysis was the overall mortality. The PTX specific mortality, the primary patency, the amputation free survival (AFS), and the target lesion revascularization (TLR) rates were additionally evaluated. Results A total of 124 patients were treated by BMS deployment, while the Eluvia platform was preferred in 75 subjects. In both groups the majority presented with lifestyle limiting claudication (BMS: 84% vs Eluvia: 73%, p = 0.73). Chronic total occlusions were more frequent in patients treated by BMS (BMS: 71% vs Eluvia: 84%, p = 0.027), whereas the calcification burden (BMS: 81% vs Eluvia: 76%, p = 0.43) and the median lesion length (in mm, IQR) (BMS: 160 (100 to 240) vs Eluvia: 140 (80 to 229), p = 0.17) were comparable. At 24 months, the overall survival (BMS: 93% vs Eluvia: 89%, hazard ratio (HR): 1.20, 95% confidence interval (CI): 0.55 to 2.64, p = 0.64) and the PTX specific survival (BMS: 95% vs Eluvia: 95%, HR: 1.28, 95% CI: 0.41 to 4.02, p = 0.67) did not differ significantly between the two platforms. No significant difference was observed regarding the 24 months primary patency rate (BMS: 66% vs Eluvia: 78%, HR: 0.65, 95% CI: 0.37 to 1.15, p = 0.18), the freedom from TLR (BMS: 83% vs Eluvia: 89%, HR: 0.81, 95% CI: 0.39 to 1.68, p = 0.572), and the AFS (BMS: 93 vs Eluvia: 89%, HR: 1.20, 95% CI: 0.55 to 2.64). The Cox regression analysis revealed a higher mortality risk among patients with chronic limb-threatening ischemia (CLTI) (HR: 3.14, 95% CI: 1.61 to 6.14, p = 0.008), chronic obstructive pulmonary disease (COPD) (HR: 4.65, 95% CI: 2.14 to 10.09, p = 0.001), in octagenerians (HR: 4.40, 95% CI: 1.92 to 10.44, p = 0.005), and in patients not on statins at baseline (HR: 2.44, 95% CI: 1.19 to 4.99, p=0.014). Conclusions In this cohort, the use of the Eluvia DES did not increase the risk for mortality compared to BMS deployment. CLTI, COPD, advanced age, and the lack of statin therapy at baseline were associated with a higher risk for death.